Sistem Informasi Manajemen Laundry Berbasis Web untuk Optimalisasi Operasional Usaha Menggunakan Metode Waterfall - Aditya Tazkia Aulia Mufid; Apriade Voutama (TIN: Terapan Informatika Nusantara, 2026)
The operational management of micro, small, and medium-sized laundry businesses that still rely on manual recording methods constitutes a fundamental problem affecting operational efficiency, data accuracy, and service quality. Freelance Laundry, as the research subject, faces challenges including transaction recording errors, difficulty in tracing customer data, and delays in compiling operational reports. This study aims to design and implement a web-based laundry management information system capable of optimizing the management of transaction data, customer information, service packages, and financial reports within a single integrated platform. System development was carried out using the Waterfall method, comprising the stages of requirements analysis, design, implementation, testing, and maintenance. The system design employed Unified Modeling Language (UML), including use case diagrams and Entity Relationship Diagrams (ERD). The system was developed with three user roles admin, cashier, and owner each with distinct functions and access rights. Testing was conducted using the Black Box Testing method across 15 test scenarios covering all functional modules of the system. The test results demonstrated a 100% success rate across all tested features, including user authentication, customer data management, transaction processing, and financial report export. This system has proven capable of reducing manual recording errors, accelerating administrative processes, and improving the accuracy of operational data management at Freelance Laundry.